Atomically dispersed zincophilic sites in N,P-codoped carbon macroporous fibers enable efficient Zn metal anodes - Zeng, Yinxiang (2023)
Zn dendrite growth and undesired parasitic reactions severely restrict the practical use of deep-cycling Zn metal anodes (ZMAs). Herein, we demonstrate an elaborate design of atomically dispersed Cu and Zn sites anchored on N,P-codoped carbon macroporous fibers (denoted as Cu/Zn-N/P-CMFs) as a three-dimensional (3D) versatile host for efficient ZMAs in mildly acidic electrolyte. The 3D macroporous frameworks can alleviate the structural stress and suppress Zn dendrite growth by spatially homogenizing Zn2+ flux. Moreover, the well-dispersed Cu and Zn atoms anchored by N and P atoms maximize the utilization as abundant active nucleation sites for Zn plating. As expected, the Cu/Zn-N/P-CMFs host presents a low Zn nucleation overpotential, high reversibility, and dendrite-free Zn deposition. The Cu/Zn-N/P-CMFs-Zn electrode exhibits stable Zn plating/stripping with low polarization for 630 h at 2 mA cm-2 and 2 mAh cm-2. When coupled with a MnO2 cathode, the fabricated full cell also shows impressive cycling performance even when tested under harsh conditions.